Changes in soil properties and carbon fluxes following afforestation and agriculture in tropical forest. (April 2021) - Ahirwal, Jitendra; Kumari, Sneha; Singh, Ashutosh Kumar; Kumar, Adarsh; Maiti, Subodh Kumar
Graphical abstract: Highlights: Land use change from forest to afforestation and agriculture decreases soil quality. SOC stock decreased by 84% in afforested mine soil and 50% in agriculture soil. Soil infiltration rate, total nitrogen and clay content indicate soil quality. Both afforested mine soil and agricultural soils are carbon negative. Long-term afforestation is needed for the recovery of SOC pool. Abstract: Anthropogenic land use change (LUC) affects soil quality and the global carbon (C) pool. Such LUC is a potential threat for forest ecosystems because it can alter soil biome and increases the emission of greenhouse gasses (GHGs). Here, we investigated the changes in soil quality and CO2 emission following afforestation of reclaimed coal mine land and agriculture land created in a tropical dry deciduous forest of Jharkhand, India. Soil samples were collected from afforested mined soil (AMS), agriculture soils (AGS), and the natural forest soils (NFS) and analyzed for physicochemical and biological properties. Soil infiltration rate and CO2 efflux were recorded in situ, and C balance and emission coefficient (C i ) were calculated to determine soil C dynamics. Our results demonstrated significant alteration in soil quality parameters (decreases/increases based on the individual parameter) in converted land use. Compared to NFS, soil organic carbon (SOC) stocks decreased by 84% in AMS and 50% in AGS, soil CO2 efflux increased by 35% in AGS and decreased by 43% in AMS, attributed to differences in vegetation and microbial activities among sites. Principal component analysis showed soil infiltration rate, total nitrogen, and clay content were highly influenced by the LUC and explicitly indicate soil quality. The 4-year old AMS was C negative and had a greater C i value than AGS and NFS, probably due to the lesser vegetation cover and adverse soil properties. We concluded that the conversion of tropical forests to different lands altered soil quality that can be assessed using indicator parameters like soil infiltration rate, total nitrogen, and clay content. Such LUC tends to switch the forest from a sink to a source of CO2 whether the end use is afforestation or agriculture. However, land degradation due to surface mining activities had a greater impact on soil quality and C sequestration potential than agriculture.